Statistics education in medical sciences - BEKİROĞLU, GÜLNAZ NURAL (My University, 2002)
Kniest syndrome is a type of dwarfism that is characterized by unusually short arms and legs,a round face with hollow or depressed areas, swelling and stiffness of the joints and a stiff drawing up (contractures) of the fingers. Cleft palate, abnormal curvature of spine (scoliosis), and vision and/or hearing problems may also occur. Intellect is usually normal in people with this syndrome. In this case report we present the audiologic findings of an eight-year-old boy with Kniest syndrome
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Klinik Tıp (MED); Klinik Tıp; TIBBİ BİLİŞİM; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL INFORMATICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Tıbbi Bilişim; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Health Informatics; Family Practice; Medicine (miscellaneous); General Medicine; Kniest syndrome; Hearing loss; Audiological evaluation